Pengaruh Content Marketing Dan E-Marketing Melalui Live Streaming Tiktok Terhadap Keputusan Pembelian : (Studi Kasus Pengguna Aplikasi TikTok Di Kaliabang Bekasi) - Achir, Irvan Fadhil; Navanti, Dovina; Woelandari, Dewi Sri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
With the rapid development of global marketing, businesses are required to design digital marketing strategies to support conventional marketing. This study aims to determine the influence of content marketing and e-marketing through TikTok live streaming on purchasing decisions. The method used in this study is a quantitative method with a positivist approach to test the hypothesis and analyze the influence of independent variables on dependent variables through mediating variables. The results of this study indicate that Content Marketing (X1) and E-Marketing (X2) have a significant influence on both the Live Streaming (Z) variable and the Purchase Decision (Y) variable.